Diabetes Alters Activation and Repression of Pro- and Anti-Inflammatory Signaling Pathways in the Vasculature - Di Marco, Elyse; Gray, Stephen P.; Jandeleit-Dahm, Karin (Frontiers in Endocrinology, 2013)
A central mechanism driving vascular disease in diabetes is immune cell-mediated inflammation. In diabetes, enhanced oxidation and glycation of macromolecules, such as lipoproteins, insults the endothelium and activates both innate and adaptive arms of the immune system by generating new antigens for presentation to adaptive immune cells. Chronic inflammation of the endothelium in diabetes leads to continuous infiltration and accumulation of leukocytes at sites of endothelial cell injury. We will describe the central role of the macrophage as a source of signalling molecules and damaging by-products which activate infiltrating lymphocytes in the tissue and contribute to the pro-oxidant and pro-inflammatory micro-environment. An important aspect to be considered is the diabetes- associated defects in the immune system, such as fewer or dysfunctional athero-protective leukocyte subsets in the diabetic lesion compared to non-diabetic lesions. This review will discuss the key pro-inflammatory signalling pathways responsible for leukocyte recruitment and activation in the injured vessel, with particular focus on pro- and anti-inflammatory pathways aberrantly activated or repressed in diabetes. We aim to describe the interaction between advanced glycation end products (AGEs) and their principle receptor RAGE, Angiotensin II (Ang II) and the Ang II type 1 receptor (AT1R), in addition to reactive oxygen species (ROS) production by NADPH oxidase (Nox) enzymes that are relevant to vascular and immune cell function in the context of diabetic vasculopathy. Furthermore, we will touch on recent advances in epigenetic medicine that have revealed high glucose-mediated changes in the transcription of genes with known pro-inflammatory downstream targets. Finally, novel anti-atherosclerosis strategies that target the vascular immune interface will be explored; such as vaccination against modified LDL and pharmacological inhibition of ROS producing enzymes.